The Narration in the novel Vertigo by Ahmed Murad - قاسم, رزان; نضال القصيري, (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The narration is the main pillar upon which the fictional work is built. It brings together all the artistic components (time, place, personality, etc.). It has close ties to description and dialogue; Therefore, the way the narrative is used, and the novelist's identification of his narrative style, plays a major role in conveying the idea of ​​the novel. In this research, we will approach the narration technique in the novel Vertigo, by the Egyptian writer Ahmed Murad, and identify the narrative pattern that he worked on in this novel, and how to employ it, without neglecting the techniques of description and dialogue. This is because the fictional work cannot be what it is without narration, description and dialogue. In this research, we relied on the descriptive approach, which is concerned with describing the studied phenomenon objectively, discussing and analyzing it, in order to find positive results that contribute to the development of scientific research. What is the narrative pattern that Murad followed in the novel, and how did he employ it in it؟